Generalized cattaneo’s law over a vertical cylinder on casson fluids - Husna Izzati, Osman; Ching, Dennis Ling Chuan; Nur Fatihah, Mod Omar; Vieru, Dumitru; Zulkhibri, Ismail (Penerbit Akademia Baru, 2022)
The analysis of unsteady axial symmetric flows of an incompressible and electrically conducting Casson fluid over a vertical cylinder with time-variable temperature, under influence of an external transversely magnetic field has been carried out. The mathematical model is build based on the time-fractional differential equation of Cattaneo’s law with Caputo derivative to describe thermal transport. Based on the model, we can obtain the effect of temperature gradient history on heat transport and fluid motion. Besides, the generalized mathematical model that we build can be used to achieve the Classical Cattaneo’s law. Comparison between the generalized Cattaneo and the classical Cattaneo was examined to optimize the heat transport model.